Experimental investigation into stud shear connections under combined shear and tension forces. (June 2017) - Shen, M.H.; Chung, K.F.
Abstract: In order to investigate structural behaviour of stud shear connections with both solid and composite slabs under combined shear and tension forces, a systematic experimental investigation with a total of six test series are conducted. These include 11 standard push-out tests where the shear connections are under shear forces, and 11 modified push-out tests where the shear connections are under combined shear and tension forces. It should be noted that the testing method of the standard push-out tests recommended in EN 1994-1-1 is adopted, and headed shear studs are installed in either "favourable" or "unfavourable" positions of decking troughs. Test results of all the 22 push-out tests are fully presented, and these include typical modes of failure, measured load-slippage curves as well as shear resistances of the test specimens. It is found that the shear resistance of the shear connection should be reduced with a factor of 0.84 for the case of a solid concrete slab, and a factor of 0.75 for the case of a composite slab, provided that the tension force Tn is smaller than or equal to 0.267 Qm where Qm is the shear resistance of the shear connection. These data will be adopted in subsequent numerical investigations for calibration of advanced finite element models. These models will then be used to perform parametric studies on stud shear connections with a wide range of geometrical configurations and loading conditions to provide additional data for formulation of design rules. Highlights: In order to investigate structural behaviour of stud shear connections with both solid and composite slabs under combined shear and tension forces, a systematic experimental investigation with a total of six test series are conducted. The experiment work include 11 standard push-out tests where the shear connections are under shear forces, and 11 modified push-out tests where the shear connections are under combined shear and tension forces. Test results of all the 22 push-out tests are fully presented, and these include typical modes of failure, measured load-slippage curves as well as shear resistances of the test specimens. It is found that the shear resistance of the shear connection should be reduced with a factor of 0.84 for the case of a solid concrete slab, and a factor of 0.75 for the case of a composite slab, provided that the tension force Tn is smaller than or equal to 0.267 Qm where Qm is the shear resistance of the shear connection. These data will be adopted in subsequent numerical investigations for calibration of advanced finite element models. These models will then be used to perform parametric studies on stud shear connections with a wide range of geometrical configurations and loading conditions to provide additional data for formulation of design rules.